Distribution and numbers of wintering sea ducks in Swedish offshore waters - Nilsson, Leif (Ornis Svecica, 2012)
The first survey of seaducks covering the offshore waters of the entire Baltic was undertaken in 1992/1993, when, however, the Swedish waters were covered with relatively few ship surveys. The second all Baltic survey 2007–2011 included extensive aerial surveys of all Swedish offshore waters. This paper presents the Swedish data from these two surveys, supplemented with data from several other but partial surveys back to the early 1970s. The most numerous wintering seaduck in the Swedish waters was the Long-tailed Duck Clangula hyemalis with an estimated population of 1.41 million in 1992/1993, decreasing with 69% to 0.44 million in 2007–2009. Hoburg bank south of Gotland and the two Midsjö banks accounted for the vast majority of these ducks. In 2009–2011 only small numbers of scoters Melanitta fusca and M. nigra were found in Swedish Baltic waters. The totals for the Eider Somateria molissima and Red-breasted Merganser Mergus serrator were estimated at 20,000 and 8,000, respectively. Larger numbers of Eiders (50,000) and scoters (20,000) were found on the west coast.